Comparative In Vitro Evaluation Of Different Brands Of Metformin Hydrochloride Film Coated Tablets Marketed In Addis Ababa, Ethiopia - Abatea, Kassa; Temesgen, Abrham; Nigatu, Muluken (Asian Journal of Pharmaceutical Research and Development, 2020)
Metformin hydrochloride is a biguanide class of drug widely used to treat Type 2 diabetes mellitus. Its oral bioavailability is about 50 to 60 % with a half-life of about 3 h. This study focused on evaluation and comparison of the physicochemical properties of different brands of metformin hydrochloride (500mg) film coated tablets available in drug retail outlets in Addis Ababa, Ethiopia. Some different in vitro tests including hardness, weight variation, disintegration time, dissolution study, and assay were conducted as per United States Pharmacopeia. To compare dissolution profiles of the generic products against the innovator product (product A), a model independent method, similarity factor (f2), was also used. Weight variation result showed that all brand fall within the 5% limit from the average which is acceptable. Disintegration time of less than 15 minutes was observed for all brands. The in vitro drug release study results for the products ranged between 82 and 93% release within 30 minutes which is above 80% limit as per the United States Pharmacopeia requirement. The similarity f2 values for generic products ranged from 53 to 75%. Furthermore, assay value of the studied brands varied from 95.60 to 104.37% which was within standard limit (95-105%). It can be concluded that all brands of metformin hydrochloride tablets met pharmacopoeial specification for the tested parameters of physicochemical properties like weight variation, hardness of tablets, disintegration time, drug release study and assay.